2-Amino-1,3,4-thiadiazoles as prospective agents in trypanosomiasis and other parasitoses - Serban Georgeta (Acta Pharmaceutica)
Parasitic diseases are a serious public health problem affecting hundreds of millions of people worldwide. African trypanosomiasis, American trypanosomiasis, leishmaniasis, malaria and toxoplasmosis are the main parasitic infections caused by protozoan parasites with over one million deaths each year. Due to old medications and drug resistance worldwide, there is an urgent need for new antiparasitic drugs. 1,3,4-Thiadiazoles have been widely studied for medical applications. The chemical, physical and pharmacokinetic properties recommend 1,3,4-thiadiazole ring as a target in drug development. Many scientific papers report the antiparasitic potential of 2-amino-1,3,4-thiadiazoles. This review presents synthetic 2-amino-1,3,4-thiadiazoles exhibiting antitrypanosomal, antimalarial and antitoxoplasmal activities. Although there are insufficient results to state the quality of 2-amino-1,3,4-thiadiazoles as a new class of antiparasitic agents, many reported derivatives can be considered as lead compounds for drug synthesis and a promise for the future treatment of parasitosis and provide a valid strategy for the development of potent antiparasitic drugs.